Investigation of serum neopterin levels and adenosine deaminase enzymatic activity in measles infection - Narin, D.; Cosgun, Y.; Korukluoglu, G.; Kavutcu, M. (International Journal of Biology and Chemistry, 2023)
The aim of this study was to investigate the serum neopterin level and ADA activity in acute measles infection and determine whether there is a correlation between the measles optical density values, and the neopterin and ADA levels. The neopterin level and ADA activities were investigated in the samples of 136 measles IgM-positive patients along with those of 40 measles IgM-negative patients as the control group. The most important findings of the study was the determination of significantly higher neopterin levels and ADA activity in the measles IgM-positive group when compared to the measles IgM-negative group. These findings have shown that the neopterin level and ADA activity can assist in the diagnosis of measles in the acute period as biomarkers.